Validation of Management Progress on IEG Evaluation Recommendations : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2022)
The Management Action Record (MAR) is a key element of the World Bank Group’s accountability framework. The MAR supports accountability in the follow-up of Independent Evaluation Group (IEG) evaluation recommendations by enabling meaningful tracking, dialogue, and self-assessment of World Bank Group management’s implementation of IEG recommendations. There are 15 evaluations in this year’s MAR. The document covers IEG’s synthesis of progress toward achieving IEG evaluations’ intended outcomes and its assessment of the approach and evidence in management’s MAR report entitled Using Evaluative Evidence to Deliver Development Outcomes: A World Bank Group Management Report on Implementation of IEG Recommendations FY17-21.